Corella i el «Tirant»: qüestions d'intertextualitat - Carles Miralles (Caplletra: Revista Internacional de Filologia, 2015)
The article points out that the presence of Corellian fragments in Tirant does not only affect his published works,but also those that were never printed and that must have been orally transmitted. The author finds evidence of oral performance, and of a constant amplifying and simplifying process of a hypo-text, which seems to reflect an ornamental, free and creative use of paragraphs that does not influence the narrative flow.